The Prevalence of Root Sensitivity following Periodontal Therapy: A Systematic Review - Y. H. Lin; D. G. Gillam (International Journal of Dentistry)
The reported prevalence of dentine/root (hyper)sensitivity (DH/RS) in the published literature varies, and this may be due in part to a) the different study populations and (b) the different methodologies employed in evaluating the pain response. According to von Troil et al. (2002) there are limited data available in terms of the prevalence and intensity of DH/RS following periodontal therapy. Objectives. The aim of the present study was therefore to review the literature in order to identify all relevant studies for inclusion and to determine whether there was any evidence of DH/RS following periodontal procedures in the published literature up to 31st December 2009 using an agreed search protocol. Methods. 840 papers were identified, from searching both electronic databases (PUBMED) and hand searching of relevant written journals. Twelve papers were subsequently accepted for inclusion. Results. The results of the present study would indicate that the reported prevalence for DH/RS (following nonsurgical therapy) was between 62.5% and 90% one day after treatment decreasing to approximately 52.6% to 55% after one week. The prevalence of DH/RS following surgical therapy was between 76.8% and 80.4% one day after treatment subsequently decreasing over time to 36.8% after 1 week, 33.4% after 2 weeks, 29.6% after 4 weeks, and 21.7% after 8 weeks. Conclusions. It is evident from reviewing the included studies that patients may suffer from mild discomfort following periodontal procedures although both the prevalence and intensity of DH/RS may vary depending on the duration and the type of procedure involved. Most of the studies included in this paper would tend to suggest that DH/RS may be relatively mild/moderate in nature and transient in duration.